Neuromyelitis optica spectrum disorder safely and successfully treated with satralizumab during pregnancy and breastfeeding: a case report - Yoshida, Takashi; Watanabe, Osamu; Nomura, Miwa; Yoshimoto, Yusuke; Maki, Yoshimitsu; Takashima, Hiroshi (Frontiers in Neurology, 2023)
Background Satralizumab, a monoclonal antibody that recognizes interleukin-6 receptors, is known to reduce the relapse rate in neuromyelitis optica spectrum disorder (NMOSD), but its safety during pregnancy has not been established. We present the case of an NMOSD patient who safely completed pregnancy, parturition, and breastfeeding under satralizumab treatment. Importantly, satralizumab transfer to umbilical cord blood, infant serum, or breast milk was not observed. Case presentation A 37-year-old Japanese female developed anti-aquaporin 4 antibody-positive NMOSD with left optic neuritis. Despite responding to steroid and azathioprine therapy, she experienced moon face and weight gain and desired the prompt reduction of the steroid dosage. She also wanted to conceive a child with a safe and preferably early pregnancy and parturition. Because pregnancy and parturition after the onset of NMOSD elevate the risk of relapse and miscarriage, treatment with satralizumab was initiated with the patient's consent. She experienced normal parturition and continued with satralizumab, steroid, and azathioprine treatments while breastfeeding without experiencing any relapses. Concentrations of satralizumab in the umbilical cord blood, infant serum, and breast milk were below the detection sensitivity. Conclusion These findings suggest that satralizumab may be safe and effective for the perinatal management of NMOSD, especially when there are concerns about continuing pregnancy and the risk of relapse after parturition.